Application of Decision Tree C4.5 to determine post-Madrasah Aliyah students' college majors (case study: Madrasah Aliyah Misbahul Ulum) - Tasya Mulyani; Bustami; Sujacka Retno (Proceedings of International Conference on Multidisciplinary Engineering (ICOMDEN), 2024)
This research aims (1) To apply Decision Tree C4.5 in determining post-Madrasah Aliyah students' college majors (2) To find out the results of applying the C4.5 Decision Tree Method in determining post-Madrasah Aliyah students' college majors (3) To design a system decision support to simplify and speed up the process of analyzing student data to determine post-Madrasah Aliyah students' college majors. This system was developed using the PHP programming language by applying the C4.5 Decision Tree algorithm method. Decision Tree is a machine learning algorithm that uses a set of rules to make decisions with a tree-like structure with the concept of presenting the algorithm with conditional statements, which includes branches to represent decision-making steps that can lead to profitable results by determining the value of entropy, split info and he gain ratio of this research produces objective results. Involving students from class 12 odd semesters, this research resulted in the identification of engineering majors for each student. Keywords: C4.5 algorithm, decision tree, php, system